Revision of Nearctic Dasysyrphus Enderlein (Diptera: Syrphidae) - Locke, Michelle M.; Skevington, Jeffrey H. (Zootaxa, 2013)
Dasysyrphus Enderlein (Diptera: Syrphidae) has posed taxonomic challenges to researchers in the past, primarily due to their lack of interspecific diagnostic characters. In the present study, DNA data (mitochondrial cytochrome c oxidase sub-unit I—COI) were combined with morphology to help delimit species. This led to two species being resurrected from syn-onymy (D. laticaudus and D. pacificus) and the discovery of one new species (D. occidualis sp. nov.). An additional new species was described based on morphology alone (D. richardi sp. nov.), as the specimens were too old to obtain COI. Part of the taxonomic challenge presented by this group arises from missing type specimens. Neotypes are designated here for D. pauxillus and D. pinastri to bring stability to these names. An illustrated key to 13 Nearctic species is presented, along with descriptions, maps and supplementary data. A phylogeny based on COI is also presented and discussed.